Women candidates and party nomination trends in India: evidence from the 2009 general election - Spary, Carole (Taylor and Francis, 2014)
More women MPs than ever before were elected to the lower house of the national parliament of India in the 2009 General Election. Yet, the increase in women’s presence in the Lok Sabha cannot necessarily be attributed to the increased willingness of political parties to field more women candidates, despite rhetorical party political support for increasing women’s participation in political institutions. This article analyses party political nomination of women as candidates in the 2009 election, and finds significant variations in levels of nomination across parties and across India’s states. The article also examines in detail the nomination of female candidates by the two largest political parties, the Indian National Congress party and the Bharatiya Janata Party, both of which support proposals for introducing reserved seats for women in national and state legislatures. The findings reject the proposition that parties only nominate women in unwinnable seats, but finds support for the proposition that parties are risk averse when it comes to nominating women, and that this can restrict the number of women nominated for election. The article concludes with some further questions for future research on gender and political recruitment in India.